2017
DOI: 10.1002/jts.22195
|View full text |Cite
|
Sign up to set email alerts
|

Beta Blocker Administration During Emergency Department Evaluation for Acute Coronary Syndrome Is Associated With Lower Posttraumatic Stress Symptoms 1‐Month Later

Abstract: We examined whether beta blocker administration in the emergency department (ED) during evaluation for suspected acute coronary syndrome (ACS) was associated with posttraumatic stress disorder (PTSD) symptoms 1 month later. Participants (N = 350) were enrolled in the Reactions to Acute Care and Hospitalization (REACH) study, an ongoing observational cohort study of ED predictors of medical and psychological outcomes after evaluation for suspected ACS. Beta blockade during evaluation in the ED was extracted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Participants in the current report were enrolled in the study between November 2013 and February 2016. Prior work, focusing on acute stress (13), threat perception (14)(15)(16)(17)(18), posttraumatic stress disorder (19)(20)(21)(22)(23)(24), and the ED environment (25,26), within this cohort has been published. This is the first examination of sleep within this cohort.…”
Section: Methodsmentioning
confidence: 99%
“…Participants in the current report were enrolled in the study between November 2013 and February 2016. Prior work, focusing on acute stress (13), threat perception (14)(15)(16)(17)(18), posttraumatic stress disorder (19)(20)(21)(22)(23)(24), and the ED environment (25,26), within this cohort has been published. This is the first examination of sleep within this cohort.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, clinical trials reported that propanol treatment with memory reactivation therapy reduced PTSD symptoms [217,218]. Beta-blocker administration for the suspected acute coronary syndrome was also shown to reduce PTSD symptoms at 1-month follow-up [219]. However, research on the preventative effects of propranolol is contradictory.…”
Section: Potential Anti-inflammatory Therapeutic Approachesmentioning
confidence: 99%
“…Additionally, certain medications administered during hospitalization for cardiovascular events may impact risk for subsequent PTSD. 25 Recent research demonstrated that individuals administered benzodiazepines in-hospital following acute coronary syndrome (ACS) were nearly 4 times more likely to develop PTSD in response to ACS than those not given benzodiazepines. 26 Benzodiazepines are commonly prescribed on demand during hospitalization following a medical trauma 27 ; understanding their impact on stroke-induced PTSD may have important implications for in-hospital PTSD risk screening.…”
Section: Introductionmentioning
confidence: 99%